SToRytelliing to Improve Disease outcomes in Gout (STRIDE-GO) in African American veterans with gout: a trial study protocol - Jasvinder A. Singh (BMC, 2021)
Abstract Objective Medication adherence in gout is suboptimal, and the lack of effective interventions to address it presents a huge challenge. Medication adherence and gout outcomes are worse in racial/ethnic minorities. The objective of this paper was to provide the details of the study protocol for randomized, controlled trial (RCT) in African Americans (AAs) with gout that will test the effectiveness of a culturally appropriate gout storytelling intervention. Methods The SToRytelliing to Improve Disease outcomes in Gout (STRIDE-GO) study will be a 12-month, multicenter, open-label RCT that will assess the effect of a culturally appropriate gout storytelling in at least 300 AA veterans with gout. Participants will be randomized to gout-storytelling intervention vs. a stress reduction video in a 1:1 ratio. The primary outcome is urate-lowering therapy (ULT) adherence measured with MEMSCap™, an electronic monitoring system (efficacy, 6 months; sustenance of efficacy, 12 months). Secondary outcomes include gout flares, serum urate (SU), gout-specific health-related quality of life [HRQOL], self-reported ULT adherence, patient satisfaction with treatment, and patient understanding of the intervention. AA veterans with gout who met the 1977 Preliminary American College of Rheumatology (ACR) classification criteria for gout, currently prescribed an oral ULT medication (allopurinol or febuxostat) for at least 6 months, and not using a pillbox to redistribute their medications, will be invited to an in-person study visit. After the study coordinators obtain informed consent, and ensure that participants meet the inclusion criteria, the eligible participants will be provided with their current ULT in a MEMSCap™ bottle for the 1-month run-in period and asked to return to the clinic in 1 month. ULT adherence with MEMSCap™ will be recorded at a 1-month return visit. Interested participants will complete the baseline assessments, randomized using the computerized system to either gout-storytelling intervention or a stress reduction intervention video arm and watch the respective video in-clinic. Patients will be interviewed on the phone at 2 and 4 months regarding the viewing of the videos at home at each time. Participants will be assessed in-clinic at 3, 6, 9, and 12 months; MEMSCap™ data and patient surveys will be captured at each visit. For any missed visit, assessments will be completed on the phone and MEMSCap™ data captured at the next in-clinic visit. Discussion The study will assess the efficacy of a behavioral intervention to improve ULT adherence in minority populations with gout. Trial registration ClinicalTrials.gov NCT 02741700. Registered on 14 September 2018